Quantitative Intracerebral Hemorrhage Localization - Muschelli, John (Stroke, 2015)
BACKGROUND AND PURPOSE: The location of intracerebral hemorrhage (ICH) is currently described in a qualitative way; we provide a quantitative framework for estimating ICH engagement and its relevance to stroke outcomes. METHODS: We analyzed 111 patients with ICH from the MISTIE II clinical trial. We estimated ICH engagement at a population level using image registration of CT scans to a template and a previously labeled atlas. Predictive regions of NIHSS and GCS stroke severity scores, collected at enrollment, were estimated. RESULTS: The percent coverage of the ICH by these regions strongly outperformed the reader-labeled locations. The adjusted R(2) almost doubled from 0.129 (reader-labeled model) to 0.254 (quantitative-location model) for NIHSS and more than tripled from 0.069 (reader-labeled model) to 0.214 (quantitative-location model). A permutation test confirmed that the new predictive regions are more predictive than chance: p<.001 for NIHSS and p<.01 for GCS. CONCLUSIONS: Objective measures of ICH location and engagement using advanced CT imaging processing provide finer, objective, and more quantitative anatomic information than that provided by human readers.